Wide voltage-gain range asymmetric H-bridge bidirectional DC-DC converter with common ground for energy storage systems - Zhang, Yun; Gao, Yongping; Li, Jing; Sumner, Mark (Korean Institute of Power Electronics, 2018)
A wide-voltage-conversion range bidirectional DC-DC converter is proposed in this paper. The topology is comprised of one typical LC energy storage component and the special common grounded asymmetric H-bridge with four active power switches/anti-parallel diodes. The narrow output PWM voltage is generated from the voltage difference between two normal (wider) output PWM voltages from the asymmetric H-bridge with duty cycles close to 0.5. The equivalent switching frequency of the output PWM voltage is double the actual switching frequency, and a wide step-down/step-up ratio range is achieved. A 300W prototype has been constructed to validate the feasibility and effectiveness of the proposed bidirectional converter between the variable low voltage side (24V~48V) and the constant high voltage side (200V). The slave active power switches allow ZVS turn-on and turn-off without requiring any extra hardware, and the maximum conversion efficiency is 94.7% in the step-down mode and 93.5% in the step-up mode. Therefore, the proposed bidirectional topology with a common ground is suitable for energy storage systems for example for renewable power generation systems or electric vehicles with a hybrid energy source.